1983
DOI: 10.1901/jaba.1983.16-243
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Assessment of Children's Compliance to Teachers' Requests and Consequences for Compliance

Abstract: Naturally occurring levels of teacher commands, child compliance to those commands, and positive and negative teacher feedback were studied in 19 teachers and 130 children in kindergarten through third grade. Seventy-five of the children had been identified as "making a good social adjustment" to school (high-rated) and 55 children were identified as "not making a good social adjustment" to school (low-rated). Results of intensive observation over a 4-wk period showed that: (a) individual teachers differed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 8 publications
(14 reference statements)
1
45
0
1
Order By: Relevance
“…The corollary was that punishment did not work. Accumulated data, however, attest to the continued frequent use of negative feedback in dassroom environments (Strain, Lambert, Kerr, Stagg, & Lenker, 1983;White, 1975), to the efficacy of negative consequences for managing problematic behavior (e.g., Azrin & Powers, 1975;Drabman & Spitalnik, 1973;Iwata & Bailey, 1974;Rapport, Murphy, & Bailey, 1982;Van Houten, Nau, MacKenzieKeating, Sameoto, & Colavecchia, 1982), and to the failure of attempts to conduct dasses using only positive consequences (e.g., Becker, Madsen, Arnold, & Thomas, 1967;Hall et al, 1971;Rosen, O'Leary, Joyce, Conway, & Pfiffner, 1984;Sajwaj, Twardosz, & Burke, 1972). In the most recent attempt, Rosen et al (1984) demonstrated repeatedly that when special education teachers stopped providing negative feedback to students This research was supported in part by a grant from the Middle Country School District No.…”
mentioning
confidence: 99%
“…The corollary was that punishment did not work. Accumulated data, however, attest to the continued frequent use of negative feedback in dassroom environments (Strain, Lambert, Kerr, Stagg, & Lenker, 1983;White, 1975), to the efficacy of negative consequences for managing problematic behavior (e.g., Azrin & Powers, 1975;Drabman & Spitalnik, 1973;Iwata & Bailey, 1974;Rapport, Murphy, & Bailey, 1982;Van Houten, Nau, MacKenzieKeating, Sameoto, & Colavecchia, 1982), and to the failure of attempts to conduct dasses using only positive consequences (e.g., Becker, Madsen, Arnold, & Thomas, 1967;Hall et al, 1971;Rosen, O'Leary, Joyce, Conway, & Pfiffner, 1984;Sajwaj, Twardosz, & Burke, 1972). In the most recent attempt, Rosen et al (1984) demonstrated repeatedly that when special education teachers stopped providing negative feedback to students This research was supported in part by a grant from the Middle Country School District No.…”
mentioning
confidence: 99%
“…Additionally, when the rate of instruction is too low (approximately .75) compliance also drops (Atwater & Morris, 1988). Strain et al (1983) observed the natural rate of instruction in kindergarten rooms and noted that all of the teachers they observed elicited commands averaging from .2 to 2.5 commands per minute. These results closely match the recommended instruction rates for optimal compliance; however, the current study identified somewhat different rates of instruction for average preschool age children.…”
Section: Discussionmentioning
confidence: 96%
“…While some studies look at commands as one category (Strain et al, 1983), others break commands into only those of alpha and beta type (Williams & Forehand, 1984;Forehand et al, 1979;Peed et al, 1977), while other studies have indicated that a more specific command type may effect compliance (Kuczynski & Kochanska, 1990b). Very few studies have combined command form (direct, indirect, question etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations